Using Public Health Data for Soil Pb Hazard Management in Ohio. Issue 2 (March 2018) - Obrycki, John F.; Serafini, Tyler; Hood, Darryl B.; Alexander, Chris; Blais, Pam; Basta, Nicholas T.
Abstract : Objectives: To evaluate how frequently elevated soil lead (Pb) hazards (≥400 ppm Pb) were identified in existing blood Pb site investigations in Ohio. Design: This study evaluated 3050 site investigations from the Ohio Department of Health for children with blood Pb levels at or above 10 μg dL −1 that contained bare soil Pb data. Setting: Data were collected from existing databases maintained by the Ohio Department of Health. Participants: All data were de-identified prior to analysis. The data used included blood Pb level test results for children (18 years or younger) in Ohio, with most data coming from children younger than 6 years. Main Outcome Measures: The main outcome measures were blood Pb levels and identified Pb concentrations in environmental media, including soil, paint, and dust. Methods: Data were organized and summarized according to county. Summary statistics were generated on the basis of type of environmental media and county. Results: Soil samples were collected in approximately 5% of all blood Pb cases in Ohio between 1999 and 2015. Median bare soil Pb was 1030 mg Pb kg −1 (range, 0-345 021 mg Pb kg −1 soil). Fifty-six of Ohio's 88 counties had at least 1 soil sample above 10 000 ppm (mg Pb kg −1 ). Multiple Pb hazards were identified, including bare soil (74% frequency), deteriorated exterior Pb paint (74%), deteriorated interior Pb paint (72%), and settled Pb dust (72%). Bare soil collected from identified dripline areas contained 2638 ppm Pb above soils collected from bare soil play areas ( P = .02). Ninety assessments (3%) contained a bare soil hazard, with no other identified hazards. No trend was found comparing county mean or median Pb with county population. Previously identified high-risk counties for elevated blood Pb levels did not have an elevated prevalence of bare soil Pb hazards compared with other counties ( P = .64). Conclusions: Site investigators should anticipate finding and managing elevated bare soil Pb in locations throughout Ohio. When communicating with the public about bare soil Pb hazards, practitioners and policy makers should emphasize the importance of addressing all potential Pb exposure sources. Findings demonstrate the importance of the individual home environment for exposure, as previously identified high-risk counties for elevated blood Pb levels were not different from other counties. Abstract : Supplemental Digital Content is Available in the Text.